Analisis Kebutuhan Pengembangan Komik Digital Matematika Berbasis Deep Learning Untuk Siswa Kelas III SD - Gusti Ayu Sri Wijastini; I Komang Wahyu Wiguna; I Putu Suardipa (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study was motivated by the need for mathematics learning media that can connect abstract concepts with the concrete experiences of third-grade elementary school students. In the research context, mathematics instruction was still largely procedural, while the available media did not fully support conceptual understanding, active engagement, and mindful, meaningful, and joyful learning experiences. This study aimed to identify the empirical and pedagogical needs for developing a digital mathematics comic based on pedagogical deep learning for third-grade elementary school students. A descriptive qualitative approach was employed as a preliminary study in the analysis stage of the ADDIE model. The data sources included third-grade teachers, third-grade students, learning documents, teaching materials, and students’ learning achievement records. Data were collected through classroom observation, interviews, documentation studies, and systematic field notes. The data were analyzed through data reduction, data display, verification, and conclusion drawing. Data trustworthiness was strengthened through source triangulation, technique triangulation, and member checking. The findings indicate that a digital mathematics comic is needed because students require visual-narrative, contextual, interactive, and user-friendly media to understand units of length, units of weight, units of time, and simple fractions. Teachers also need practical media that are aligned with the Merdeka Curriculum and capable of presenting guiding questions, authentic contexts, character dialogues, concept visualization, short exercises, and learning reflection. The main contribution of this study lies in mapping the developmental needs of a digital mathematics comic based on pedagogical deep learning before the product design stage. Therefore, the findings provide an initial foundation for developing mathematics learning media that are not only visually engaging but also pedagogically grounded and appropriate for the characteristics of elementary school students.